Impact of Diet Composition on Insulin Resistance - Conde, Silvia V.; Martins, Fatima O. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Insulin resistance is a key player in the pathology of cardiometabolic diseases - obesity, hypertension, dyslipidaemia, type 2 diabetes and NAFLD. These diseases are commonly associated with a peripheral insulin resistance, but an important role of insulin is played at brain circuitries that control food behaviour and autonomic activity. Brain insulin resistance is also associated with cognition impairment and Alzheimer Disease and other neurodegenerative diseases. Disruptions in diet composition, e.g. hypercaloric diets, and patterns, as well as nutritional status contribute to the genesis of insulin resistance. In contrast, hypocaloric diets, different feed regimens and some nutrients have beneficial impacts on insulin resistance and disease development. This special issue "Impact of diet composition on insulin resistance" is developed to compile studies that highlight the beneficial or deleterious impact of different nutritional plans on insulin sensitivity and metabolism and that unravel mechanistic links between diet composition and nutritional status and the development of insulin resistance, both periphery and centrally.